EKSPLORASI ALAT MUSIK GARANTUNG PADA PEMBELAJARAN BANGUN GEOMETRI MENGHITUNG VOLUME BALOK - Napitupulu, Eastman; Tambunan, Hardi (Universitas Quality, 2023)
The purpose of this study is to explore the integration of mathematics with culture through the traditional musical instrument of the Batak Toba ethnic group, one of which is the